Kristina Peuschel, Anne Burkard (Hrsg.): Sprachliche Bildung und DaZ in den geistes- und gesellschaftlichen Fächern. Tübingen: narr Studienbücher 2019. 259 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Büşra Çakıl: Die Rehabilitierung des Ehrbegriffs. Baden-Baden: Tectum 2018. 210 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Christine Garbe: Lesekompetenz fördern. Stuttgart: Reclam 2020.129 S. - Albus, Vanessa (Zeitschrift für Didaktik der Philosophie und Ethik)

Die Nutzung digitaler Medien aus der Perspektive der Lehrkräfte - Drossel, Kerstin; Eickelmann, Birgit; Niemann, Jan; Vennemann, Mario (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Sichtweisen von Lehrkräften zum Lernen und Lehren mit digitalen Medien - Niemann, Jan; Eickelmann, Birgit; Drossel, Kerstin (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Lehrerausbildung zum Lernen und Lehren mit digitalen Medien - Drossel, Kerstin; Eickelmann, Birgit; Labusch, Amelie; Niemann, Jan (ICILS 2018 #NRW. Vertiefende Analysen und Befunde für Nordrhein-Westfalen im internationalen Vergleich)

Controversial Histories – Current Views on the Crusades. Engaging the Crusades, Volume Three.

Das Heilige, die Gewalt und die Liebe in der neuen Kultur des Sichtbaren. Fritz Langs/Thea Harbous "Metropolis" und Bertolt Brechts "Die heilige Johanna der Schlachthöfe" - Morrien, Rita (Weimarer Beiträge)

Neither demarcation nor confrontation. Finding a critical position towards right-wing populism - Haker, Christoph; Otterspeer, Lukas (Zeitschrift für Weiterbildungsforschung)
Abstract Right-wing populism has strongly polarizing effects in politics, education and science—a problem which this article aims to adress. Instead of claiming a demarcation between science and education on the one hand and right-wing populist ideology on the other, we initially focus on continuities. At the same time, we are concerned with finding a critical distance towards right-wing populism. Using the theoretical framework of boundary-work we therefore analyse a case of right-wing populist educational and scientific efforts. Boundary-work can occur in an institutional, content-related and epistemic dimension. While we identify strong continuities in the institutional and content-related dimensions, we see the main difference in the epistemic dimension. In conclusion, we use the results of our analysis to develop a critical position as scientists and educationists towards right-wing populism, drawing consequences for the epistemic, content-related and institutional dimensions.
Keywords: General Earth and Planetary Sciences; General Environmental Science

Right-Wing Populism and Educational Research. Exploring theoretical and methodological perspectives - Haker, Christoph; Otterspeer, Lukas (Zeitschrift für Diskursforschung)